Board Of Commissioners Characteristics And Financial Statement Fraud In Indonesian Soes - Siti Fatimah; Indira Januarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of the size of the board of Commissioners, the gender diversity of the board of Commissioners, the financial competence of the board of Commissioners, and the political connections of the board of Commissioners on fraudulent financial reports in non-financial SOEs listed on the Indonesia Stock Exchange for the 2018-2023 period. The observation data in this study were 120 observations. The analysis tool uses logistic regression. The results of this study show that board size and gender diversity have a negative effect on financial statement fraud. Financial competence does not have a negative effect, and political connections do not positively affect fraud involving financial statements.